Risk Factors for Prediabetes among Women of Childbearing Age in DKI Jakarta (Analysis of SISKOHATKES Data 2023) - Sholihah, Nur; Simanjorang, Chandrayani; Dewanti, Balqis Triaya; Muthia, Firda; Azis, Arkanaya Alya; Priyastiwi, Risdiana (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Abstract Background: Prediabetes in women of childbearing age (15—49 years) is a serious health issue that can affect fertility, pregnancy, and long-term health. This study aims to identify the factors influencing the incidence of prediabetes among the Hajj pilgrims in DKI Jakarta.Method: This cross-sectional study utilized data from the Integrated Hajj Health Information System (Siskohatkes) 2023, with a minimum sample size of 976. The study used Cox Regression analysis to determine the Prevalence Ratio (PR) and assess the association between independent and dependent variables at the multivariate level.Result: In 2023, the prevalence of prediabetes among women of reproductive age in the Hajj pilgrim’s population in DKI Jakarta was 29.4%. Multivariate analysis indicated that High-Density Lipoprotein (HDL) cholesterol (Adjusted PR=1.33; 95%CI=1.00—1.78), triglycerides (Adjusted PR=1.38; 95%CI=1.08—1.77), and employment status (Adjusted PR=2.25; 95%CI=1.06—4.75) were associated with the incidence of prediabetes in this population.Conclusion: These results underscore the necessity for special attention to risk factors such as HDL cholesterol, triglycerides, and job status in the prevention and management of prediabetes among women of childbearing age, particularly within the hajj pilgrim community.